In Lessing’s Footsteps: Dramaturgy in Germany and Britain - Michael Raab (Université Toulouse - Jean Jaurès, 2021)
The first part of the essay outlines the history of dramaturgy in Germany and Britain, the second part deals with the different new writing policies there.